Bulgaria - Accelerating Bulgaria's Convergence : Volume 2. The Challenge of Rasing Productivity - World Bank (Washington, DC, 2012)
The report aims to assist the Bulgarian authorities in identifying options for policies and reforms that would help to boost productivity and employment and thereby economic growth and income convergence. To achieve this, the report looks at Bulgaria's product and labor markets, human resource development, and R&D and innovation system. The reform options are arranged along a time dimension, ranging from short to medium term. The implications of the proposed policy options for the government's budget are also briefly explored, including the utilization of EU grant funds. The report concentrates mostly on the supply-side aspects of Bulgaria's product and labor markets, its education (primary and general secondary, VET, tertiary) delivery, and its R&D and innovation system.